Land-use rights of foreign-invested enterprises according to Vietnamese law - CHAU THI KHANH (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The provisions of Vietnamese law are presented, with a focus on the fundamental issues directly related to the land-use rights of foreign-invested enterprises, such as how land-use rights are established and the rights of foreign-invested enterprises in using land, the trading of rights for foreign-invested enterprises, and the securing of land-use rights of foreign-invested enterprises.Method: The term "doctrinal research" is used to describe a technique that systematically explains the rules that apply to a certain area of law, examines the connections between those rules, offers explanations for any ambiguities, and, perhaps, foresees how those rules will evolve in the future.Findings: The value of land in economic production cannot be overstated. For all intents and purposes in Vietnam, land-use rights are equivalent to property rights in the law. Using a doctrinal research approach, this paper explains the current State of land law in Vietnam, with specific attention paid to the rights of foreign-invested enterprises to use land. For a foreign-owned business to be granted land use rights in Vietnam, it must first have an investment project in Vietnam that has been approved by the relevant Vietnamese government agency, and that requires the land in question. Both the State, acting on behalf of the landowner, and the land’s actual owners can establish the land-use rights. In general, only the State can grant a foreign-invested company the legal authority to use its land. There are fewer opportunities for those who must rely on intermediaries to gain access to land use rights.Implications/Novel Contribution: The paper offers solutions so that businesses with foreign investment can better understand the potential legal risks associated with land-use rights.